Marxism and intersectionality race, gender, class and sexuality under contemporary capitalism - Bohrer, Ashley J. (Philosophy (Transcript (Firm)), 2019)
"What does the development of a truly robust contemporary theory of domination require? Ashley J. Bohrer argues that it is only by considering all of the dimensions of race, gender, sexuality, and class within the structures of capitalism and imperialism that we can understand power relations as we find them nowadays. Bohrer explains how many of the purported incompatibilities between Marxism and intersectionality arise more from miscommunication rather than a fundamental conceptual antagonism. As the first monograph entirely devoted to this issue, "Marxism and Intersectionality" serves as a tool to activists and academics working against multiple systems of domination, exploitation, and oppression"--